STOCK ANALYSIS OF FINE SHRIMP Metapenaeus elegans de Man (1907) USING YIELD PER RECRUIT RELATIVE MODEL (Y’/R) AT SEGARA ANAKAN LAGOON CILACAP CENTRAL JAVA - Suradi Wijaya Saputra (JOURNAL OF COASTAL DEVELOPMENT, 2010)
The research of stock analysis of Metapenaeus elegans was held in Segara Anakan Lagoon, Cilacap CentralJava. This research were aimed to study the carapace length of optimal capture, exploitation rate optimumand maximum sustainable yield relative. The research were carried out by using survey method and thesample were collected by systematic random sampling method. Sampling conducted over 11 months, fromFebruary until December 2004. Data was analyzed using ELEFAN in FiSAT II software. The result showthat rate of exploitation of M. elegans was 0.83 / year, and the length of first capture of the M. elegans was14.5 mm. At 14.5 mm carapace length, the rate of exploitation (E) should be 0.51 / year, and E0.1 was 0.47 /year. The average biomass of exploited for 24% of the initial biomass, which has exceeded the ideal limit of10% (E0.1 concept). According to the above three indicators (the carapace length of shrimp, exploitation rateand biomass used), then the exploitation of M. elegans in Segara Anakan Lagoon has been consideredseriously over-exploited. The rate of exploitation has reached 154% of Emsy and 177% of E0.1. Based onsimulation results, the size of carapace length of first capture that produces the MSY is a minimum carapacelength of 21.3 mm, and the rate of exploitation (E) can reach 0.7 / year.